PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN INTERAKSI DAN PEMAHAMAN SISWA KELAS XI SMA NEGERI 2 TOMPASO - Limbong, Trya Ona Sari; Mamangkey, Jefry J; Maramis, Alfonds Andrew (SOSCIED, 2025)
This classroom action research was conducted to enhance learning interaction and conceptual understanding among eleventh-grade students through the implementation of a jigsaw cooperative learning model supported by visual media at SMA Negeri 2 Tompaso. The study followed a cyclical research procedure comprising four distinct phases: systematic planning, strategic implementation, structured observation, and critical reflection. The research involved 25 participants from class XI F1 during the odd semester of the 2025/2026 academic year. The findings demonstrated substantial improvement in both student engagement and comprehension between the initial and subsequent cycles. The classical mastery percentage showed remarkable progress, increasing from 40% in Cycle I to 88% in Cycle II. This significant enhancement provides compelling evidence that the jigsaw cooperative learning approach, when effectively integrated with visual media, serves as a powerful pedagogical strategy for improving both interactive learning dynamics and conceptual mastery of human digestive system material among senior high school students. The research outcomes clearly indicate that the synergistic combination of cooperative learning structures and visual media support creates an optimal learning environment that fosters active participation and deepens conceptual understanding in biology education